Penilaian Kesehatan Bank Digital Menggunakan CAMEL dan RGEC - Samuel Martono (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the health level of digital banks listed on the Indonesia Stock Exchange (IDX) using the CAMEL and RGEC methods to assess which digital banks are good investment choices. The CAMEL method assesses aspects of capital, asset quality, management, profitability, and liquidity, while the RGEC method covers risk profiles, good governance, profitability, and capital. The objects of this study are nine digital banks listed on the Indonesia Stock Exchange: Bank Jago, Bank Aladin Syariah, Allo Bank, Bank MNC Internasional, Amar Bank Indonesia, Bank Raya, Bank Neo Commerce, Bank Capital Indonesia, and Bank QNB Indonesia. The observation period is 2019 to 2023 and the research data is obtained from the financial statements of the nine digital banks for the period 2019-2023. The results of the study indicate that there are four banks that have a stable health level throughout the current period and therefore can be good choices for investment: Bank Neo Commerce, Bank Raya, Bank Capital, and Bank MNC Internasional. Abstract This study aims to analyze the health level of digital banks listed on the Indonesia Stock Exchange (IDX) using the CAMEL and RGEC methods to assess which digital banks are good investment choices. The CAMEL method assesses aspects of capital, asset quality, management, profitability, and liquidity, while the RGEC method covers risk profiles, good governance, profitability, and capital. The objects of this study are nine digital banks listed on the Indonesia Stock Exchange: Bank Jago, Bank Aladin Syariah, Allo Bank, Bank MNC Internasional, Amar Bank Indonesia, Bank Raya, Bank Neo Commerce, Bank Capital Indonesia, and Bank QNB Indonesia. The observation period is 2019 to 2023 and the research data is obtained from the financial statements of the nine digital banks for the period 2019-2023. The results of the study indicate that there are four banks that have a stable health level throughout the current period and therefore can be good choices for investment: Bank Neo Commerce, Bank Raya, Bank Capital, and Bank MNC Internasional.